2019
DOI: 10.1021/acssuschemeng.8b06133
|View full text |Cite
|
Sign up to set email alerts
|

Eco-Friendly Fabrication of Plasmonically Active Substrates Based on End-Grafted Poly(ethylene glycol) Layers

Abstract: We report completely sustainable processes and materials for inexpensive and scalable fabrication of plasmonically active solid substrates, which are critical for emerging applications in sensing, catalysis, and metasurfaces. Our approach involves grafting of poly(ethylene glycol) (PEG) onto silicon oxide terminated solid substrates using all-water based processing leading to an ultrathin (12 nm) and smooth (roughness of ∼1 nm) functional layer. The resulting surfaces facilitate robust and effective immobiliza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…For a grafting density of 0.36 chain/nm 2 , the distance between grafting sites is 1.88 nm, which is smaller than twice the radius of gyration of PEG (R g = 6.9 nm), confirming that end-grafted PEG layers are in the brush regime. 43 Note that the grafting density of ∼0.36 chain/nm 2 and height of 19.3 nm are significantly high when compared with previously reported homogeneous PEG layers 44 prepared by spin-coating of similar materials.…”
Section: Resultsmentioning
confidence: 75%
“…For a grafting density of 0.36 chain/nm 2 , the distance between grafting sites is 1.88 nm, which is smaller than twice the radius of gyration of PEG (R g = 6.9 nm), confirming that end-grafted PEG layers are in the brush regime. 43 Note that the grafting density of ∼0.36 chain/nm 2 and height of 19.3 nm are significantly high when compared with previously reported homogeneous PEG layers 44 prepared by spin-coating of similar materials.…”
Section: Resultsmentioning
confidence: 75%
“…These results suggest that AgNPs facilitate plasmonic hot spots that effectively concentrate electromagnetic fields at/near the metallic surfaces and increase the signal amplitude by several orders of magnitude. 56,57 To understand the effect of Ag NP concentration on the SERS activity, the Raman spectrum was measured after a 1 mM MB analyte molecule was dropped on NF mats prepared using different Ag loadings. As shown in Figure 6b, the highest intensity of the SERS spectrum of MB was obtained after utilizing of a NF with 1 wt %.…”
Section: Resultsmentioning
confidence: 99%
“…This situation necessitates the development of SERS substrates with green synthesis methods that include environmentally friendly materials and processes. Green synthesis, especially the ones based on plant extracts, is the ideal approach due to availability and renewability of a wide range biomass, as well as the environmental friendliness of post-synthesis waste products. Therefore, there is a growing number of studies that report the preparation of various SERS-active substrates using green techniques and materials. Ankamwar et al reported the green synthesis of Ag nanoparticles (NPs) using the plant extract as reducing and stabilizing agents and employed it as an effective SERS substrate as well as a catalyst. , In another study, Ag NPs are reduced on graphene oxide using the leaf extract of Psidium guajava and used as a SERS platform to detect methylene blue …”
Section: Introductionmentioning
confidence: 99%